2021
DOI: 10.7717/peerj.11798
|View full text |Cite
|
Sign up to set email alerts
|

Precocious puberty in male wild boars: a possible explanation for the dramatic population increase in Germany and Europe

Abstract: Background The wild boar population in Europe is steadily growing, one of the reasons for this increase probably being the high reproductive potential of this large mammal. Population management is important to stabilise wild boar numbers and a great deal of attention is focusing on the reasons, which might contribute to the high reproductive rates. Understanding the timing of puberty attainment provides information required for proper management practices. Knowledge of the earliest expected tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…One possible reason for the delay of sexual maturation in SEAL3 is her slower initial growth and lower body mass at age compared with normal individuals. It is reported that body weight has a more important role than age in driving the maturation of testes in wild bores (Sus scrofa) [33]. Nutritional condition is known to work as a permissive factor for the timing and progression of pubertal development in humans (Homo sapiens) [2].…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for the delay of sexual maturation in SEAL3 is her slower initial growth and lower body mass at age compared with normal individuals. It is reported that body weight has a more important role than age in driving the maturation of testes in wild bores (Sus scrofa) [33]. Nutritional condition is known to work as a permissive factor for the timing and progression of pubertal development in humans (Homo sapiens) [2].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also relied on the classification and results obtained in a previous publication in which the attainment of puberty was defined according to the stage of spermatogenesis [ 8 ]. We categorized males as prepubertal when the weight and the age of the animal were less than 26 kg and 8 months, i.e., 29.6 ± 3.6 kg, and 9.3 ± 1.2 months, which correspond to the limits for pubertal animals [ 7 , 8 ]. On the other hand, individuals whose weight and age were more than 34 kg and 10 months were defined as postpubertal, these values being typical of sexually mature individuals [ 5 , 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Germany, the wild boar breeding season occurs between autumn and winter, i.e., from about October until January [ 6 ] when the day length is shortened, with farrowing approximately four months later between the end of winter and spring, which coincides with February until May. Recent investigations showed that piglets of both sexes reach puberty from about six to nine months of age and sexual maturity already in their first year of life; however, almost none of these studies evaluated sex hormones [ 6 , 7 , 8 ]. In fact, puberty was assessed macro- and microscopically in wild boar females by determining the diameter and presence of follicles/corpora lutea, i.e., the stage of the estrus cycle [ 6 , 9 ], whereas in males, it was determined by assessing the stage of spermatogenesis by means of histology and immunohistochemistry of the anti-Müllerian hormone and androgen receptor [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations